Analogiese taal by Bultmann in die lig van die kennissosiologie 1 - Malan, Gert (Hervormde teologiese studies, 2000)
A reflection on Bultmann's use of analogical language in thelight of the sociology of knowledge. Bultmann's approach to analogical language, or as he put it, mythological language, was to demythologise it. Reaction to his demythologising program was largely negative, as it seemed radical to many. This study shows that Bultmann's approach to analogical language does not differ much from the way the concept "analogical language" is used within the sociology of knowledge. It seems that disciplines which had previously been practised in isolation from each other, developed their own terminology. The result is that essentially the same issueswere referred to by different names, and that the same terms could be used todenote different issues. In this article the question whether analogical/mythological/symbolical/metaphorical language is treated in much the same way by thetwo different approaches is answered positively.